Effects of cholesterol-supplemented and unsupplemented diets containing unextracted and extracted Syzygium cumini seeds on lipid profiles of alloxan-induced diabetic albino rats - Madhuri A Agnihotri; Aqueel Khan (Universiti Kebangsaan Malaysia, 2015)
Background: Hypercholesterolemia and hyperlipidemia are the major problems associated with diabetes. Various agents are being tried to solve these so that problems related to micro- and macroangiopathy can be averted. Plant fibers particularly water-soluble gummy fibers have been reported earlier to reduce blood lipids and cholesterol levels in normal and diabetic animals and humans. Objective: Effects of cholesterol-supplemented and unsupplemented diets containing unextracted and extracted Syzygium cumini seeds on lipid profiles of alloxan-induced diabetic albino rats Material and Methods: Powder of Syzygium cumini seeds was successively extracted using organic solvents, and hypolipidemic and hypocholesterolemic activities of 15% unextracted, 15% extracted, and 15% degummed S. cumini seeds with cholesterol-supplemented and unsupplemented diets were assayed in normal and alloxan-induced diabetic rats. Result: In this study, significant decrease in the levels of total serum cholesterol, serum triglycerides, serum phospholipids, and total cholesterol and triglycerides in tissues of liver, heart, and aorta was observed. Also, significant increase was observed in the phospholipid levels in tissues of liver, heart, aorta, and biliary, and fecal bile acid content and sterols in normal and alloxan-induced diabetic rats. Conclusion: The hypocholesterolemic and hypolipidemic effects of S. cumini seeds may be attributed to their watersoluble gel-forming gummy fiber acting by decreasing cholesterol absorption and breakdown leading to an increased fecal excretion of bile acids and sterols.